Association between localised retinal nerve fibre layer defects and cardiovascular risk factors - Shin, Joo Youn (Sci Rep, 2019)
Localised retinal nerve fibre layer defects (RNFLDs) are reported to indicate the degree of glaucomatous damage but can also be sequelae of retinal vascular insufficiency as a result of systemic vascular factors. We investigated the association between RNFLDs and cardiovascular risk factors. RNFLDs were detected in 440 (29.2%) of 1508 subjects. The presence of RNFLDs was associated with higher HbA(1c) (odds ratio [OR] 1.289, p < 0.001), higher 24-h mean systolic blood pressure (SBP; OR 1.013, p < 0.005), and lower estimated glomerular filtration rate (eGFR; OR 0.995, p < 0.005). An increasing number of RNFLDs was correlated with higher SBP (r = 0.186, p < 0.001), higher HbA(1c) (r = 0.128, p < 0.010), lower eGFR (r = −0.112, p < 0.020), and younger age (r = −0.303, p < 0.001). Subjects with RNFLDs had a higher predicted 10-year risk of atherosclerotic cardiovascular disease than did those without RNFLDs (9.7% vs 7.9%, p = 0.008 in middle-aged subjects, 25.6% vs 23.2%, p = 0.040 in older subjects). In conclusion, RNFLDs are associated with SBP, eGFR, and HbA(1c). Concomitant cardiovascular risk factors should be considered when evaluating patients with localised RNFLDs.